Faktor-Faktor Penentu Pertumbuhan pada Balita yang Mengalami Stunting Setelah Pemberian Makanan Olahan Berbasis Hewan dalam Makanan Pendamping sebagai Upaya Meningkatkan Kesehatan Masyarakat - Warsini Warsini; Budi Kristanto (An Idea Health Journal, 2026)
Background: Stunting is a persistent public health issue, linked to impaired growth in children, especially in developing countries. Insufficient protein intake is a primary factor limiting optimal growth in stunted toddlers. Early nutritional intervention with animal-based protein supplementation is considered a promising strategy to improve anthropometric outcomes. Methods: The study evaluated the impact of animal-based complementary feeding on anthropometric outcomes among stunted toddlers at Community Health Center Jayengan, Surakarta. A quasi-experimental, one-group pretest– posttest design was employed, enrolling 30 stunted toddlers through purposive sampling. The intervention involved administering animal-based processed complementary feeding (MP-ASI) for 30 days. Anthropometric parameters measured included body weight, height, and mid-upper arm circumference (MUAC). Data analysis utilized the Shapiro–Wilk test for normality and paired t-test, with statistical significance set at p < 0.05. Results: All anthropometric parameters showed significant improvement following the intervention. Mean body weight increased from 10.15 ± 1.20 kg to 10.85 ± 1.25 kg (p = 0.001). Mean height increased from 81.50 ± 2.80 cm to 82.90 ± 2.85 cm (p < 0.001). Mean MUAC increased from 14.80 ± 1.10 cm to 15.90 ± 1.15 cm (p = 0.002). Conclusion: Animal-based complementary feeding significantly enhances anthropometric outcomes among stunted toddlers, demonstrating a moderate effect size. This intervention represents a practical and scalable approach to support stunting reduction initiatives at the primary healthcare level.